MEDICINAL HERBS OF PASIR MAYANG, JAMBI: ETHNOPHARMACY AND TOXICITY SCREENING - HILMAN AFFANDI; ARIF NURYADIN; SUSILO B. PRAYOGO (SEAMEO BIOTROP, 2004)
This article presents the results of an investigation concerning the use of herbal medicinal plants by the people of Pasir Mayang, sub-District (Municipality) of VII Koto, District of Tebo, Jambi Province, Sumatera. The data collection was based on interviews with the healers and other villagers of Pasir Mayang who possess knowledge of the different plants and their medicinal uses. The study recorded 57 species of medicinal plants used in Pasir Mayang. The detailed uses of the 57 medicinal plants are given. All plant species were subjected to phytochemical analysis and toxicity tests, and the outcome of the analysis on the presence of alkaloids, saponins, steroids/terpenoids, and the level ofÂ toxicity against brine shrimp (Anemia salina) are presented. A comparison with other studies reported in the literature seems to indicate that a high frequency of the use of leaves in therapy may be a part of a larger cultural phenomenon among the tropical forest tribes of Southeast Asia. Keywords : Indonesia/Jarabi/Pasir Mayang/medicinal plants/ethuophannacy/toxicity screening